Pelatihan Software Proteus bagi Anggota IAEETA: Strategi Inovatif Pengembangan SDM untuk Transportasi Berkelanjutan - Kurniawan, Didik Sulistyo; Fatonah, Feti; Wildan, Muh.; Purwaningtyas, Dian Anggraini; Cahyono, Ferry Budi; Eriyandi, Eriyandi; Toni, Toni; Sulaiman, Muhammad Arif; Wahyudi, Johan; Nugrahayani, Tiara (Politeknik Penerbangan Indonesia Curug, 2025)
Human resource development through technology mastery is an innovative strategy to support the creation of sustainable transportation. This Community Service (PkM) activity carries the theme ‘Proteus Software Training for IAEETA Members: Innovative Strategies for Human Resource Development for Sustainable Transportation’. The main problem faced by partners is their limited mastery of Proteus software, particularly in terms of installation, initial configuration, use of the Virtual Oscilloscope, and integration with Arduino IDE, which is highly relevant in the fields of air navigation and aviation electrical systems. The implementation methods included module development, interactive lectures, demonstrations, hands-on practice, and project-based learning. The training results showed an increase in participants' competence from moderate to good, as reflected in their success in completing simple projects such as flashing LED simulations and signal analysis using virtual measuring instruments. A satisfaction survey also showed that the majority of participants gave a score of 4–5 in terms of material, instructors, learning methods, and facilities. This activity produced outputs in the form of training modules (printed and digital), simulation products, PkM reports, and publication articles. Thus, this training not only improved the technical skills of the participants but also strengthened the contribution of academics in supporting innovation and sustainability in transportation through the development of human resources based on simulation technology.